Análisis económico del presupuesto institucional mediante indicadores financieros en el GAD Municipal del cantón Baba durante el periodo 2018 – 2019 - Holguin Rizzo, Diana Yelena (2020)
The Autonomous Municipal Decentralized Government of the Baba canton (GAD Baba), is located on Calle 9 de Octubre 156 and Av. Guayaquil, in front of the central park of Baba. It is an entity in charge of fulfilling the essential purposes, serving and satisfying the needs of citizens, planning the physical development of the canton and its urban and rural areas, ensuring the material well-being of the community and taking care of local interests. This case study is called "Economic analysis of the institutional budget through budgetary financial indicators in the Autonomous Decentralized Municipal Government of Canton Baba during the period 2018 - 2019" Through this research, it focuses on analyzing the financial management of the entity to measure the efficiency and effectiveness of the resources obtained and invested, there will be the proper information, the same that is delivered by the institution, the data collected comes from the budgetary certificates, with this obtaining of information the financial indicators will be carried out, which will help to conclude this work. The methodology to be used is descriptive in nature, thus helping to consider the facts, obtaining specific information from the institution to be analyzed, in the same way, the field details and documentation based on files that rest in said institution, which allowed collecting the necessary information from clear and reliable way. This case study was carried out with the objective of providing knowledge on the economic analysis of the institutional budget through financial indicators in the Autonomous Decentralized Municipal Government of Canton Baba during the period 2018 - 2019, framed by the model of financial, tax and social commitment management as line of research.